2021
DOI: 10.1097/gox.0000000000003705
|View full text |Cite
|
Sign up to set email alerts
|

Warm Weather and Surgical Site Infections: A Meta-analysis

Abstract: Background: Seasonal variability, in terms of warm weather, has been demonstrated to be a significant risk factor for surgical site infections (SSIs). However, this remains an underexposed risk factor for SSIs, and many clinicians are not aware of this. Therefore, a systematic review and meta-analysis has been conducted to investigate and quantify this matter. Methods: Articles were searched in Embase, Medline Ovid, Web of Science, Cochrane Central, and Google Scholar, and data were extracted from relevant stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Conversely, for BI and SSI, the peak was in the summer season. The higher ambient temperature and relative humidity during summer may facilitate the colonization and transmission of pathogens such as Acinetobacter, E. coli , and Staphylococcus aureus , thereby increasing the risk of acquiring BI and SSI [24] , [25] , [26] , [27] . These diverse time series patterns observed among different types of HAIs may help explain the inconsistencies found in previous studies regarding the seasonal peaks of HAIs [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, for BI and SSI, the peak was in the summer season. The higher ambient temperature and relative humidity during summer may facilitate the colonization and transmission of pathogens such as Acinetobacter, E. coli , and Staphylococcus aureus , thereby increasing the risk of acquiring BI and SSI [24] , [25] , [26] , [27] . These diverse time series patterns observed among different types of HAIs may help explain the inconsistencies found in previous studies regarding the seasonal peaks of HAIs [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“… 2 - 4 However, complications following total knee arthroplasty (TKA) have been found to be higher during the summer months 5 with increased risk for infections found during warmer weather. 6 - 8 In a large database study, total hip arthroplasty (THA) and TKA procedures performed in December were shown to have lower rates of complications with decreased lengths of stay postoperatively. 9 Alternatively, another study noted increased rates of periprosthetic infection following THA occur during the winter, 10 although this was not demonstrated in a population of unicompartmental knee arthroplasty patients.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, postoperative SSI occurs in approximately 1–15% of patients who undergo spinal surgery [ 3 , 4 ]. This postoperative complication could not only lead to poor prognosis of patients, but also increase medical costs [ 5 , 6 ]. The Centers for Disease Control and Prevention (CDC) is responsible for monitoring SSI.…”
Section: Introductionmentioning
confidence: 99%